Chinese Context of Research on Psychological Well-being of College Students: Literature Review and Theoretical Reflection - Wang, Qingqing; Keat, Ooi Boon (Journal of Theory and Practice in Education and Innovation, 2025)
This article systematically reviews recent literature on the psychological well-being of Chinese college students, analyzing the current situation, influencing factors, and educational models and practices. A literature review methodology is adopted to synthesize relevant research findings. The study identifies social competitive pressure and interpersonal relationship issues as two primary factors affecting the psychological well-being of college students. Innovative educational practices, such as home-school collaboration and strategies based on positive psychology, play critical roles in enhancing college students’ psychological well-being. However, psychological well-being education continues to face challenges, such as insufficient policy and institutional development, and suboptimal allocation of educational resources. The article summarizes key findings from existing studies and offers future research directions and policy recommendations to enhance the psychological well-being of college students in China.